Peroneal Nerve Function and Knee Stability after Resection Giant Cell Tumour of Proximal Fibula, A Serial Case - Mustaqim, Warih Anggoro; Isma, Satria Pandu Persada; Irsan, Istan Irmansyah (Berkala Kedokteran, 2018)
Abstract: Giant-cell Â Tumour (GCT ) is a benign Tumour, locally aggressive neoplasm which is composed of sheets of neoplastic oviod mononuclear cells uniformly distributed large, osteoclast like giant cell. Incidence GCT of proximal fibula is rare. Peroneal nerve function and stability of knee joint must be considered at the proximal fibula GCT. In 2017 we found three cases of GCT of the proximal fibula in the outpatient clinic Saiful Anwar General Hospital. All three of these patients had a confirmed GCT of proximal fibula Â which planned for Tumour resection, peroneal nerve presevation and LCL ligament reconstruction. This is study of three patients withÂ  GCT of proximal fibula was confirm with Clinical Pathological Confrence (CPC). All of patient had presented of lump,Â  slowly growing pain in lateral side of knee, limping when they walk and numbness in dorsal side of foot. One patient cannot dorsoflexion of ankle. We evaluated a peroneal nerve function and stability of knee after operation and one year after resection of tumour. All patient had occurred peroneal nerve lesion with no instability of knee post operatively. Two patient had complaint with numbness in dorsal side of foot and weakness ankle dorsoflexion and after one year both of patient had improved ankle dorsoflexion but still numbness in dorsal side of foot. One patientÂ  still complaining numbness in dorsal side of foot and weakness ankle dorsoflexion post operation and one year after operation. There is no LCL ligament instabilityÂ  in all of patient post operation and one year after operation. The peroneal nerve function and LCL ligament stability must consider when facing benign tumours in proximal fibula such as giant cell tumour proximal fibula. These resections result in an unavoidable loss of knee stability because of resecting the lateral collateral ligament (LCL) insertion site on the fibular head. Based on the literature, the incidence rate of postoperative peroneal nerve palsy ranges from 3% to 57%. Giant cell tumour in proximal fibula is rare and require wide excision with intraarticular resection of the proximal tibioï¬bular join. We must consider about peroneal nerve function and LCL ligament stability during resection of GCT proximal fibula.Â Keywords: Giant Cell Tumour Proximal Fibula, Peroneal Nerve function, LCL Ligament stability